Brefeldin A inhibits colorectal cancer growth by triggering Bip/Akt‐regulated autophagy. Issue 4 (22nd January 2019) - Zhou, Li; Gao, Wei; Wang, Kui; Huang, Zhao; Zhang, Lu; Zhang, Zhe; Zhou, Jing; Nice, Edouard C.; Huang, Canhua
ABSTRACT: Colorectal cancer (CRC) is one of the most prevalent neoplastic diseases worldwide, and effective treatment remains a challenge. Here, we found that the macrolide antibiotic brefeldin A (BFA) exhibits considerable antitumor activity both in vitro and in vivo . Induction of complete autophagic flux is characterized as a key event in BFA‐induced CRC suppression. Mechanistically, BFA provokes endoplasmic reticulum stress‐mediated binding immunoglobulin protein (Bip) expression, leading to increased Bip/Akt interaction and resultant decreased Akt phosphorylation, thereby activating autophagy. Autophagy inhibition or Bip suppression relieves BFA‐induced cell death, suggesting a key role for Bip‐regulated autophagy in the antitumor properties of BFA. Moreover, BFA acts synergistically with paclitaxel or 5‐fluorouracil in CRC suppression. Collectively, our study provides an important molecular basis for BFA‐induced autophagy and suggests that the antibiotic BFA could be repositioned as a potential anticancer drug for CRC treatment.—Zhou, L., Gao, W., Wang, K., Huang, Z., Zhang, L., Zhang, Z., Zhou, J., Nice, E. C., Huang, C. Brefeldin A inhibits colorectal cancer growth by triggering Bip/Akt‐regulated autophagy. FASEB J. 33, 5520–5534 (2019). www.fasebj.org